Construction and content validation of educational material about stuttering (Research, Society and Development, 2023)
The purpose was to build and validate the content of illustrative material to advise family members and educators of children who stutter. Study with a methodological approach, following the steps recommended in the literature for the validation of educational material. Three groups of judges were selected: eight speech therapists, 10 early childhood educators and 10 family members of stuttering children and adolescents. The judges answered a self-administered questionnaire to judge the content, language, illustrations, layout and motivation of the materials. And, after reading the folder, they should mark one of the levels of agreement (Likert scale): (1) strongly disagree, (2) disagree, (3) neither disagree nor agree, (4) agree, (5) strongly agree, and then three dichotomous questions (yes/no) associated with a space for comments/ suggestions. After organizing and categorizing the data, the Content Validity Index (CVI) was applied to measure the degree of agreement between the judges with the cut-off point of >0.78. Adjustments were necessary in the illustration and layout categories (